2017
DOI: 10.1007/s11356-017-1069-9
|View full text |Cite
|
Sign up to set email alerts
|

Degradation reaction of Diazo reactive black 5 dye with copper (II) sulfate catalyst in thermolysis treatment

Abstract: The theme of present research demonstrates performance of copper (II) sulfate (CuSO) as catalyst in thermolysis process to treat reactive black 5 (RB 5) dye. During thermolysis without presence of catalyst, heat was converted to thermal energy to break the enthalpy of chemical structure bonding and only 31.62% of color removal. With CuSO support as auxiliary agent, the thermally cleaved molecular structure was further destabilized and reacted with CuSO. Copper ions functioned to delocalize the coordination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, the effluents discharged by these industries contain untreated dyes which can be toxic to human beings and aquatic life and hence their removal from contaminated wastewater is essential. Various methods such as adsorption over activated carbon (Wen et al, 2016), thermolysis, and coagulation (Yen et al, 2017), membrane separation (Cazzorla et al, 2018;Ye et al, 2018), electrochemical decolorization (Xu L. et al, 2018), photocatalytic degradation (Liu et al, 2019), and biological treatment (Banihani et al, 2018) have been widely reported for the removal of organic pollutants. Among these methods, adsorption over activated carbon is envisaged as highly effective technique.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effluents discharged by these industries contain untreated dyes which can be toxic to human beings and aquatic life and hence their removal from contaminated wastewater is essential. Various methods such as adsorption over activated carbon (Wen et al, 2016), thermolysis, and coagulation (Yen et al, 2017), membrane separation (Cazzorla et al, 2018;Ye et al, 2018), electrochemical decolorization (Xu L. et al, 2018), photocatalytic degradation (Liu et al, 2019), and biological treatment (Banihani et al, 2018) have been widely reported for the removal of organic pollutants. Among these methods, adsorption over activated carbon is envisaged as highly effective technique.…”
Section: Introductionmentioning
confidence: 99%
“…The considerable increase in the degradation efficiency at high temperature is attributable to the production of additional radicals, which contribute to the oxidation of DV4 molecules into reaction products. According to prior studies, heat speeds up the reaction and produces more active radicals [38,39]. The activation energy (E a ) is calculated from the Arrhenius plot (not shown).…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…Very recently, Palas et al [38] reported the CWAO of reactive black 5 (100 mg L -1 ) with the aid of air and a LaNiO3 perovskite catalyst (1 g L -1 ) at 50 °C, atmospheric pressure, and pH = 3. It was found that 65.4% degradation and 89.6% decolorization were achieved in 2 h. The destruction of nitrogen to nitrogen double bonds initiated the decolorization with the for-mation of aromatic intermediates due to the smaller enthalpy of the -N=N-bonds than that of the -C=C-and -C-H bonds [39].…”
Section: Omentioning
confidence: 99%